2014
DOI: 10.5761/atcs.cr.12.02222
|View full text |Cite
|
Sign up to set email alerts
|

A Resected Case of Solitary Pulmonary Capillary Hemangioma Showing Pure Ground Glass Opacity

Abstract: A 53-year-old Japanese woman was referred to our hospital for pure ground glass opacity (GGO) in the left upper lung on computed tomography. 18F-fluorodeoxyglucose positron emission tomography revealed no abnormal uptake in the lesion. After 4 months of follow-up, we strongly suspected the lesion to be a bronchioloalveolar carcinoma and decided to perform a surgery for diagnosis. Planning to perform lingual segmentectomy by videoassisted thoracic surgery (VATS) with mini thoracotomy, we finally performed the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The affected locations were the upper lobe in two cases, the middle lobe in one case, and the lower lobe in nine cases, with tumor sizes ranging from 5 to 20 mm (mean, 10.5 mm). SPCH is characterized as a tumor that tends to appear as a single small lesion in the lower lobe, without any symptoms . According to reports on SPCH, CT revealed pure GGO in four cases and mixed GGO in six cases (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The affected locations were the upper lobe in two cases, the middle lobe in one case, and the lower lobe in nine cases, with tumor sizes ranging from 5 to 20 mm (mean, 10.5 mm). SPCH is characterized as a tumor that tends to appear as a single small lesion in the lower lobe, without any symptoms . According to reports on SPCH, CT revealed pure GGO in four cases and mixed GGO in six cases (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of radiographic appearance, the following findings were observed on chest CT: 3 cases, pure GGO; 3 cases, mixed GGO; 2 cases, a completely solid nodule; and 1 case, a cystic-solid appearance [ 2 ]. According to the report by Sakaguchi et al, 18F-fluorodeoxyglucose positron emission tomography for SPCH showed no abnormal uptake in the lesion [ 7 ]. Therefore, discriminating SPCH from these differential diagnoses based on imaging findings alone is challenging [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing incidence of this benign tumor raised the importance of preoperative diagnosis. However, SPCH is characterized by GGNs in CT images and mimics LPA radiographically [1,[3][4][5][6][7][8][9][10][11][12][13]. Even experienced thoracic surgeons and radiologists may regard SPCH as early primary lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nal diagnosis of these indeterminate lung nodules includes not only malignancies but also benign lung tumors [16]. SPCH has been an uncommon benign lung tumor, with only 17 reported cases of surgically resected SPCH before 2018 [1,[3][4][5][6][7][8][9][10][11]. However, 25 more cases have been reported in the last two years [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation